Writing environments - Dobrin, Sidney I., 1967-; Keller, Christopher J. (Book collections on Project MUSE., 2005)
"Writing Environments addresses the intersections between writing and nature through interviews with some of America's leading environmental writers. The interviews are followed by critical responses from writing scholars. This diverse range of voices speaks lucidly and captivatingly about topics such as place, writing, teaching, politics, race, and culture, and how these overlap in many complex ways."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved